Analyzing Dendritic Growth in a Population of Immature Neurons in the Adult Dentate Gyrus Using Laminar Quantification of Disjointed Dendrites - Rosenzweig, Shira; Wojtowicz, J. Martin (Frontiers in Neuroscience, 2011)
In the dentate gyrus of the hippocampus, new granule neurons are continuously produced throughout adult life. A prerequisite for the successful synaptic integration of these neurons is the sprouting and extension of dendrites into the molecular layer of the dentate gyrus. Thus, studies aimed at investigating the developmental stages of adult neurogenesis often use dendritic growth as an important indicator of neuronal health and maturity. Based on the known topography of the dentate gyrus, characterized by distinct laminar arrangement of granule neurons and their extensions, we have developed a new method for analysis of dendritic growth in immature adult-born granule neurons. The method is comprised of laminar quantification of cell bodies, primary, secondary and tertiary dendrites separately and independently from each other. In contrast to most existing methods, laminar quantification of dendrites does not require the use of exogenous markers and does not involve arbitrary selection of individual neurons. The new method relies on immonuhistochemical detection of endogenous markers such as doublecortin to perform a comprehensive analysis of a sub-population of immature neurons. Disjointed, “orphan” dendrites that often appear in the thin histological sections are taken into account. Using several experimental groups of rats and mice, we demonstrate here the suitable techniques for quantifying neurons and dendrites, and explain how the ratios between the quantified values can be used in a comparative analysis to indicate variations in dendritic growth and complexity.